Manipulating Rab GTPase activity in wheat to alter gluten quality for breadmaking - Tyler, Adam Michael (2012)
In the developing endosperm of bread wheat (Triticum aestivum), seed storage proteins are produced on the rough endoplasmic reticulum (ER) and transported to protein bodies, specialised vacuoles for the storage of protein. The important gluten proteins of wheat are transported to the protein bodies they are stored in by two distinct routes. One route consists of vesicles that bud directly off the ER, while the other involves transport through the Golgi (Arcalis et al, 2004). In plants, the RabD clade mediates ER to Golgi vesicle transport (Batoko et al, 2000).